INCREASEMENT ENTREPRENEURIAL VALUES IN SMK MUHAMMADIYAH 3 YOGYAKARTA IN THE FIELD OF BUILDING MODELING AND INFORMATION DESIGN EXPERTISE STUDENTS WITH IMPLEMENTATION OF THE “EKRENFATIHA” LEARNING MODEL - Abdul Malik; Ikhwanuddin Ikhwanuddin; Wisnu Rachmad Prihadi; Rudi Nur Syamsudin; Estu Panduaji Wijaya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to reveal the increment of entrepreneurial values in the major of Building Modeling and Information Design Expertise in SMK Muhammadiyah 3 Yogyakarta after using the implementation of the “EkRenFaTiHa” learning model. This study adopted a descriptive quantitative research design, quantitative data will be further expressed descriptively—the questionnaire data using the Likert scale assessment 4 composed of 17 aspects of entrepreneurial values. Two types of data will be obtained which are pre- and post-questionnaire. The data was analyzed by counting the average values from each aspect of entrepreneurial attitudes; then it will be converted into percentages. From this study, it is shown that there is an increase, proven by the rising average value from 17 aspects 83,33% to 85,39%. The lowest and highest range values from pre-treatment are about 75% to 96%, while the values from post-treatment are shown to be about 77% to 96%. Several aspects experienced a significant increase e.g. independent, disciplined, and communicative aspects approximately 5-8% higher than the previous. Meanwhile, risk-taking, action-oriented, hard work, cooperative, responsible, persistent, committed, and inquisitive showed a slight increase of around 1-4% higher. Nonetheless, several sectors are stable with the previous values; for instance, creative, leadership, credible, realistic, innovative, and appreciation of achievement with a range of values from 80% to 96%. From this study, it can be concluded that there is an increment from 11 entrepreneurial values after implementing the “EkRenFaTiHa” learning model, while 6 values remaining show stability; however, the average percentage from the 17 aspects overall displays an increment.